DEVELOPMENT OF INDONESIAN LANGUAGE LEARNING TEXTBOOK WITH CHARACTER EDUCATION THROUGH ACTIVE LEARNING AS AN ELEMENTARY STUDENTS’ LEARNING SOURCE - Retno Winarni; St. Y. Slamet (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This study was aimed to: (1) describe the students’ and teachers’ needs on Indonesian language learning textbook insight with character education, (2) describe the development of Indonesian language learning textbook model, (3) test the effectiveness of the textbook, 4) to describe the result of textbook dissemination. The type of the research used was research and development proposed by Borg and Gall. This research was done through 4 stages, namely: (1) exploration, (2) model development, (3) model testing, and (4) dissemination. A qualitative descriptive approach was used in the exploratory stage. In this stage, data was collected through document study, observation, interview, and questionnaire in which then analyzed using interactive analysis model. Experimental research was used in model testing stage. The results of this research were: (1) exploration stage showed that Indonesian textbooks used in Public Elementary School 15 Surakarta, Public Elementary School 02 Kleco, and Public Elementary School 2 Sumber Surakarta had not been in accordance with the students’ and teachers’ needs, (2) Indonesian textbook was developed through preliminary field testing; and (3) model testing stage was done through experimental research in the main field testing. The value of tobtained (0.43) was lower than ttable (1.64). As a result, H0 was accepted and the research was stated significant. In conclusion, Indonesian language learning textbook with character education was effective to improve students' receptive skills